Peningkatan Hasil Belajar Ciri-Ciri Bangun Datar Menggunakan Model Kooperatif Tipe Teams Games Tournament (TGT) Pada Peserta Didik di Kelas IV SDN 18 Air Tawar Selatan Kota Padang - Sandi, Nadya Refita; Masniladevi, Masniladevi; Andika, Refiona; Ahmad, Syafri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the process of improving student learning outcomes in learning the characteristics of flat shapes in class IV SDN 18 Air Tawar Selatan by using the Teams Games Tournament (TGT) Cooperative model. This research is a Classroom Action Research (PTK) that uses a quantitative approach and a qualitative approach, which is carried out in two cycles. Cycle I with two meetings and cycle II with one meeting. This research was conducted in four stages, namely planning, implementation, observation and reflection. The subjects of this research were teachers and students in class IV SDN 18 Air Tawar Selatan Padang City with a total of 17 students. Data collection techniques were carried out by analyzing documents, interviews, observations, tests, non-tests, and documentation. The data obtained were analyzed using quantitative and qualitative data analysis techniques. The results of this study showed an increase in teaching modules in cycle I with an average of 89.58% (Good) and cycle II 95.83% (Very Good). Assessment of teacher activity in cycle I with an average of 87.49% and cycle II 96.42%. Assessment of students in cycle I with an average of 85.71% and cycle II 96.42%. Assessment of learning outcomes in cycle I with an average score of knowledge, attitudes and skills is 71.69 (C), increased in cycle II to 82.68 (B). Based on these results, it can be concluded that the Teams Games Tournament (TGT) Cooperative model can improve the learning outcomes of flat building characteristics in class IV